Sistem Penyimpanan dan Pemeliharaan Arsip di Kantor Camat Kecamatan Lirik Kabupaten Indragiri Hulu - Afrida Yanis (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This journal discusses the archive storage and maintenance system at the Lirik District Office, Indragiri Hulu Regency, using qualitative methods. The results of the study indicate that the archive storage system at the Lirik District Office has implemented manual and digital storage. Physical archive storage is carried out manually by arranging it based on the principle of the origin of the archive and the type of media, taking into account the environmental conditions of the storage room (temperature and humidity). Physical archives are stored in fireproof cabinets and coded folders. Digital archives are stored via Google Drive. There are regulations set to maintain confidentiality, limit access, and maintain the cleanliness of the storage room. Archive maintenance efforts include: (1) Maintaining the storage room with air conditioning and ventilation. (2) Cleaning the storage room and archives regularly. (3) Separating damaged archives; (4) Using fireproof metal archive cabinets; (5) Arranging archives neatly and using camphor. Overall, the implementation of the archive storage and maintenance system at the Lirik District Office has met expectations, although not yet optimal. This study concludes that the archive maintenance efforts carried out are quite good in maintaining the physical condition and information of the archives, although there is still room for improvement and optimization of the system.